Two-channel ultrasonic water flowmeter based on time difference method - Liu Wei; Qin Huibin (Dianzi Jishu Yingyong, 2023)
For the small and medium diameter mono ultrasonic flowmeter due to the small number of channels vulnerable to uneven flow field distribution, a dual-channel ultrasonic water flowmeter based on the time difference method is proposed. The hardware system of the flowmeter consists of STM32L431 low-power module, high-precision timing module TDC-GP22 and other components. According to the dual-channel pipe segment structure, the data fusion method based on Kalman filter algorithm is proposed to fuse the measurement data of the two channels and complete the filtering process, which improves the measurement accuracy of the flowmeter. The experimental test shows that the flowmeter measurement error is within 2.5%, and the Kalman fusion filtering algorithm can effectively improve the flowmeter measurement accuracy.